A health-education intervention to improve outcomes for children with emotional and behavioural difficulties: protocol for a pilot cluster randomised controlled trial - Rachel Schembri; Harriet Hiscock; Frank Oberklaid; William Garvey (BMJ Open)
Introduction One in seven (14%) children aged 4–17 years old meet criteria for a mental illness over a 12-month period. The majority of these children have difficulty accessing clinical assessment and treatment despite evidence demonstrating the importance of early intervention. Schools are increasingly recognised as universal platforms where children with mental health concerns could be identified and supported. However, educators have limited training or access to clinical support in this area.Methods and analysis This study is a pilot cluster randomised controlled trial of a co-designed health and education model aiming to improve educator identification and support of children with emotional and behavioural difficulties. Twelve Victorian government primary schools representing a range of socio-educational communities will be recruited from metropolitan and rural regions, with half of the schools being randomly allocated to the intervention. Caregivers and educators of children in grades 1–3 will be invited to participate. The intervention is likely to involved regular case-based discussions and paediatric support.Ethics and dissemination Informed consent will be obtained from each participating school, educator and caregiver. Participants are informed of their voluntary participation and ability to withdrawal at any time. Participant confidentiality will be maintained and data will be secured on a password protected, restricted access database on the Murdoch Children’s Research Institute server. Results will be disseminated via peer-reviewed journals and conference presentations. Schools and caregivers will be provided with a report of the study outcomes and implications at the completion of the study.Trial registration number ACTRN12621000652875.